2022
DOI: 10.15294/jpii.v11i4.39709
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Creative Problem Solving-Flipped Classroom for Enhancing Students' Creative Thinking Skills of Online Physics Educational Learning

Abstract: Physics science differs from other educational programs. As a natural science subject, this study program has many mathematical formulas, complex scientific laws, theorems, and scientific postulates. This study program needs creative thinking skills since physics learning is related to creativity in solving scientific problems. CPS (Creative Problem Solving) and flipped classrooms are some efforts to increase creative thinking skills. In Indonesia, COVID-19 is the main reason for conducting online learning. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Refs. [22,[59][60][61] present results of using traditional flipped learning in different contexts. On average, these works have a mean of normalized learning gain of 48.38 that is lower than the 52.85 value found in this research.…”
Section: Discussionmentioning
confidence: 99%
“…Refs. [22,[59][60][61] present results of using traditional flipped learning in different contexts. On average, these works have a mean of normalized learning gain of 48.38 that is lower than the 52.85 value found in this research.…”
Section: Discussionmentioning
confidence: 99%
“…Keller's ARCS model was used in two studies (Asiksoy & Ozdamli, 2016;Asiksoy, 2018), project-based learning was implemented along with FC in three studies (Limueco & Prudente, 2018;Miller et al, 2016;Torío, 2019). Other integrated teaching methods were creative problem solving (Rahayu, 2022), peer instruction (Wood et al, 2016), team-based learning (Miller et all., 2016), gamified environment (Ahmed & Asiksoy, 2021), problem-based learning (Eldy et al, 2019;Sengel, 2016), cooperative learning (Sengel, 2016), and 5E learning cycle (Asiksoy & Ozdamli, 2017).…”
Section: Teaching Methods Integrated With Flipped Classroom Approachmentioning
confidence: 99%
“…Results of this study do not support the expectations of the 21st century, which call for students to be innovative thinkers. Various previous research results also indicate that many students have limited creative thinking skills (Rahayu et al, 2022;Botagariyev et al, 2023) Based on observations and teacher interviews in 12 schools, it was discovered that the answers provided by students to the questions were confined to those copied from the book. This is also compounded by the teacher's assignments, which only require students to answer questions in the book, preventing students from thinking creatively.…”
Section: Introductionmentioning
confidence: 98%
“…As a result, it is vital to use a learning model that can promote problem-solving skills and their impact on students' creative thinking skills. Previous research has shown that problem-based learning approaches can help students develop creative thinking skills (Nuswowati et al, 2017;Rahayu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%